Allemaal Gelogen: Feit en fictie in Bougainville (1981) van F. Springer - Dolk, Liesbeth (Acta Neerlandica, 2020)
In this article I briefly introduce the Dutch diplomat and author Carel Jan Schneider (Batavia 1932-Den Haag 2011) and his literary work. Under his pseudonym F. Springer he published fourteen books: novels and short stories. His work has been translated into French, German, Thai, Danish, Bulgarian, Slovak and Japanese. In 1995 Springer was awarded the prestigious Constantijn Huygens Prize for his complete works of fiction.In my article I will touch upon the following questions: did Schneider’s profession as a diplomat influence his way of writing and to what extent are fact and fiction interwoven in his work?